Marketing Practices and Performance of Selected Real Estate Investment Trust (REIT) Companies Towards Sustainable Real Estate Industry Framework - A. Tamayo III, Eugenio (International Journal of Management and Education in Human Development, 2023)
The pandemic has disrupted the marketing of the real estate investment trust (REIT) companies in the Philippines. The study assessed the marketing strategies of selected REITs during the pandemic on the aspects of product, price, place, promotion, people, physical evidence and process or the 7Ps of marketing. The marketing strategies were compared to what was implemented. It inferred whether these strategies contributed to sustainability, and whether they had significant connection. Post-pandemic marketing framework was suggested to increase sales and to sustain REIT business after the pandemic.